Exploring New Horizons in Professional Development: Teachers' Shifting Perspectives on Postgraduate Education - Singh, Gurdip Kaur Saminder; Sidhu , Gurnam Kaur; Ramasamy, Rajesvari; Nair , Subadrah Madhawa; Derioh, May May Grace (Journal of Ecohumanism, 2024)
The recent massive education disruptions post the pandemic have led to a significant shift on postgraduate education endeavours. Obtaining a postgraduate qualification as a form of professional development is not new. However today, it is seen in a different light. As such, this qualitative study was designed to provide a fuller narrative of 11 teachers’ views of postgraduate education as a form of their professional development post-pandemic. Findings suggest that teachers’ reasons for undertaking postgraduate education was very much tied to their self-gains rather than becoming research and empirical-driven professionals. Such a finding seemed contradictory to the theories of teacher professional development that emphasize the outcomes of effective professional development on teacher effectiveness. The findings also imply a notable shift in teachers’ preferred mode of learning post-pandemic, with online study emerging the most preferred option. The implications drawn from this research accentuate the necessity for policymakers and educational leaders to implement a more nuanced and flexible approach to teacher professional development.